The Relationship between Self-efficacy and Learning Environment with Students' Self-directed Learning - Nanda Mirzawati; Neviyarni Neviyarni; Rusdinal Rusdinal (Jurnal Aplikasi IPTEK Indonesia, 2020)
The lack of self-directed learning of students shown by students is one problem associated with self-efficacy and the learning environment. The purpose of the research is to reveal the relationship between self-efficacy and the learning environment, and self-directed learning. This study uses the correlational method and data collected from a sample of 198 students, which were found using proportional random sampling techniques. Data were collected using a self efficacy scale (24 valid items = 0.851), a learning environment scale (32 valid items = 0.830), and a self-directed learning scale (64 valid items = 0.936). Data were then analyzed using multiple regression. The results showed the correlation coefficient r = 0.535 and p = 0.00 (p> 0.05), which showed that there was a positive and significant relationship between self-efficacy and the learning environment together with self-directed learning. So it can be explained that the higher the self-efficacy and learning environment, the higher the student's self-directed learning.